WHEAT BRAN IN BAKERY PRODUCTS - Axrorova, R.Sh.; Amanov, B.N.; Amonova, Z.M.; Mardonova, S.D.; Tõlqinova, Sh.T.; Hasanova , A.Sh. (Innovative Development in Educational Activities, 2024)
In terms of water-binding capacity, bran protein flour is close to full-fat soy flour and surpasses all other protein products in this indicator. In order to create a wide range of food products with controlled composition and nutritional properties for the production of protein products, it is advisable to use raw materials that actually exist in the country - wheat bran. Protein products from bran have a high fat-binding ability to form an “oil in water” emulsion. Along with the ability to change the surface tension at the oil-water interface, bran protein products had a similar property in relation to the gas-water phases.